Human Peripheral Clocks: Applications for Studying Circadian Phenotypes in Physiology and Pathophysiology - Saini, Camille; Brown, Steven A.; Dibner, Charna (Frontiers in Neurology, 2015)
Most light-sensitive organisms on earth have acquired an internal system of circadian clocks allowing the anticipation of light or darkness. In humans, the circadian system governs nearly all aspects of physiology and behavior. Circadian phenotypes, including chronotype, vary dramatically among individuals and over individual lifespan. Recent studies have revealed that the characteristics of human skin fibroblast clocks correlate with donor chronotype. Given the complexity of circadian phenotype assessment in humans, the opportunity to study oscillator properties by using cultured primary cells has the potential to uncover molecular details difficult to assess directly in humans. Since altered properties of the circadian oscillator have been associated with many diseases including metabolic disorders and cancer, clock characteristics assessed in additional primary cell types using similar technologies might represent an important tool for exploring the connection between chronotype and disease, and for diagnostic purposes. Here, we review implications of this approach for gathering insights into human circadian rhythms and their function in health and disease.